Harvesting of Arthrospira platensis with helicoidal and straight trichomes using filtration and centrifugation. Issue 13 (1st September 2020) - Cuellar-Bermudez, Sara P.; Kilimtzidi, Evmorfia; Devaere, Jolien; Goiris, Koen; Gonzalez-Fernandez, Cristina; Wattiez, Ruddy; Muylaert, Koenraad
ABSTRACT: Arthrospira: is the most widely cultivated strain of all microalgae and cyanobacteria. Arthrospira forms helical trichomes that, under certain circumstances, can switch to a straight morphology. This study compared harvesting using filtration and centrifugation between helical and straight Arthrospira strains. Filtration using woven nylon membranes is the most commonly used harvesting method in the industry. Gravity filtration using nylon membranes resulted in a high retention efficiency for both strains, but the filtration flux was very low for the straight strain. Pumped filtration resulted in an increase in the filtration flux for both strains (12 to 20 m 3 m −2 h −1 ) but in a strong decline in the retention efficiency for the straight Arthrospira strain. The nominal pore size of the woven nylon membranes had only a minor influence on the harvesting efficiency. Centrifugation yielded a high harvesting efficiency and a solid pellet at relatively low g forces (4000 g ) for the straight strain, but efficiency was low even at high g forces for the helical strain. These results illustrate the importance of selecting the most appropriated harvesting methodology depending on Arthrospira strains' morphology. While the helical strain could be easily harvested using filtration, it is preferably to use centrifugation at low g force for the straight strain.